Numerical Study of the Flow-Induced Vibration during Tunnel Surging at the Intake Section of Chenderoh Dam - Mazlan A.Z.A.; Zawawi M.H.; Arbain A.; Ghazali M.H.M.; Satar M.H.A.; Abas M.A.; Hassan N.H.; Radzi M.R.M. (Institute of Physics Publishing, 2023)
Chenderoh Dam that located in Malaysia is one of renewable energy power plant that beneficial to mankind. However, in some cases, the dam suffers from the vibration effect during the water spilling from upstream to downstream. This study focused on major part of the dam which is the intake section during the tunnel surging condition. A detail 3D model of the intake section was constructed and used in the prediction of flow-induced vibration response. The results of frequency domain response and operational defection shapes (ODS) from the effect of flow-induced vibration are compared with the natural frequencies and mode shapes of the dam. From the results, the transient vibration responses due to the flow of water occurred at the frequency of 8.63 Hz with the maximum deformation of 8.24 x 10-1 m, meanwhile, the modal analysis obtained at 2.76 Hz of natural frequency with deformation of 9.1 x 10-4 m. The deformation of ODS is high because of the water flow and tunnel surging condition. However, there is no resonance phenomenon occurred, yet a safety precaution must still be considered by the operator based on this result. Published under licence by IOP Publishing Ltd.